Gobernanza Urbana y Participación Comunitaria. Los Casos de Barcelona, Bilbao y Pamplona (Urban Governance and Community Involvement. Cases of Barcelona, Bilbao and Pamplona) - Imanol Telleria; Igor Ahedo Gurrutxaga (Oñati Socio-Legal Series)
This article is based on a detailed study of three cases (Barcelona, ​​Pamplona and Bilbao) trying to address from a theoretical perspective a more current characterization of urban movements, joining in a framework of analysis the contributions of the American and European schools study of social movements. To do this, we present the results of empirical research conducted in the districts of the three cities and perform a comparison of the most important variables.